Integrating environmental education and environmental management. - FILHO, Walter Leal (1997)
Shows how environmental education and environmental management, two major tools of sustainable development, may be integrated. Outlines the common features of environmental education and environmental management, listing the benefits of the integration of the two methodologies. Describes some of the issues that need to be considered so that such an integration may take place.